AUTENTIKASI TRANSFORMASI PASAL 852 AYAT (1) KUHPERDATA TERHADAP PEMBAGIAN WARIS SISTEM BILATERAL DI DESA PUHKEREP KECAMATAN REJOSO - Umami, Hafidhul (USRATUNA: Jurnal Hukum Keluarga Islam, 2023)
Inheritance law is the rules that regulate a person's assets after the owner dies. In general, inheritance or distribution of inheritance can be carried out using three models, namely using patrilineal, matrilineal and bilateral or parental systems. This research aims to determine the distribution of inheritance in Puhkerep village, Rejoso subdistrict and the reasons behind it, as well as the views of Article 852 of the Civil Code on the distribution of inheritance in Puhkerep village, Rejoso subdistrict. This research is field research where the author went directly to observe, interview and research the inheritance distribution system in Puhkerep village, Rejoso subdistrict and the data was compared with KUHPer article 852 in order to find authentication between KUHPer article 852 and the findings in Puhkerep village, Rejoso subdistrict. From the results of the researchers' findings, many people in Tinampuh village, Rejoso subdistrict, share inheritance between men and women equally (1:1) because the culture in Tinampuh village, Rejoso subdistrict, on average, both men and women work equally for meet daily needs, and for heirs who inherit their parents, one share is added. According to the Civil Code article 852, the division of inheritance in Tinampuh village, Rejoso district, has a point of similarity, namely that men and women are equalized in the distribution of inheritance, however there is a slight difference, namely the addition of one share for heirs who share their parents.